2016
DOI: 10.1080/09540121.2016.1200714
|View full text |Cite
|
Sign up to set email alerts
|

Self-in-love versus self-in-stigma: implications of relationship quality and love attitudes on self-stigma and mental health among HIV-positive men having sex with men

Abstract: The present study examines the mediating effect of love attitude on the associations between relationship quality with self-stigma and mental health among HIV-positive men having sex with men (MSM). Participants included 211 HIV-positive MSM (M = 41.77 years, SD = 11.10) and they were assessed on their relationship quality, love attitudes, HIV-positive self-stigma, and mental health. Structural equation modeling showed that the model fit the data well, χ(50) = 152.80, p < .05, comparative fit index = .94, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
2
14
0
1
Order By: Relevance
“…In a sample of sexual minority adolescents, Martin-Storey and Crosnoe (2012) further revealed that those who experienced sexual orientation-based harassment were more likely to report negative self-perception, which predisposed them to depression. Similarly, findings reported that having a negative sense of self might disrupt social functioning in sexual minorities (Crawford, Allison, Zamboni, & Soto, 2002; Yang, Mak, Ho, & Chidgey, 2017).…”
Section: Psychological Mediation Frameworkmentioning
confidence: 89%
“…In a sample of sexual minority adolescents, Martin-Storey and Crosnoe (2012) further revealed that those who experienced sexual orientation-based harassment were more likely to report negative self-perception, which predisposed them to depression. Similarly, findings reported that having a negative sense of self might disrupt social functioning in sexual minorities (Crawford, Allison, Zamboni, & Soto, 2002; Yang, Mak, Ho, & Chidgey, 2017).…”
Section: Psychological Mediation Frameworkmentioning
confidence: 89%
“…A study with MSM in China newly diagnosed with HIV measured four types of HIV stigma (enacted, felt, vicarious, and internalized) and found that internalized HIV stigma to most strongly correlate with depression [62]. Two other studies also found internalized HIV stigma to strongly predict mental health [49,71]. A study with MSM living with HIV in Hong Kong measured both perceived and internalized HIV stigma and specifically focused on perceived HIV stigma within the MSM community [38].…”
Section: Hiv-related Stigma and Mental Healthmentioning
confidence: 99%
“…Sexual orientation is one of the five main causes of aggressive and violent behavior of students. However, it leads to repercussions for the healthcare area, since it involves determinants on the healthillness-care process of students (7) and implies the quality of relationships and self-esteem of young men who have sex with men, (11) which are aspects found in this study. It is up to educators and healthcare professionals to exhaustively search for information and dialogues that value peace and respect for differences.…”
Section: Discussionmentioning
confidence: 91%
“…(9) Love does not seem to be the only element of rupture of these preconditions, but the deep fragility of recognizing them-selves, caused by the violence experienced and lack of emotional support. (11) Bullying is a common problem in the education area. Sexual orientation is one of the five main causes of aggressive and violent behavior of students.…”
Section: Discussionmentioning
confidence: 99%